The Denazification of the Post-war Germany in the American Occupation Zone in 1945-1949 - Mykhailo Boiko; Oleksandr Ivanov (Європейські історичні студії, 2018)
As a result of the analysis of the documents of the American Military Administration, agreements, signed at the official governmental level by the representatives of the Allies, personal documents, articles of the German newspaper “Die Zeit” and sociological researches carried out by the scientific institutions, the authors of the article outline the main mechanisms, procedures, institutions for the implementation of the denazification and identify its advantages and disadvantages during the American occupation in 1945-1949.